Concep????es de professores do Instituto Federal do Piau?? sobre as dimens??es cultural e epistemol??gica da moda - Arag??o, Camila Maria Albuquerque (2018)
We analyze the conceptions of the teachers of the subjects of the fashion area, of the higher technology course in Fashion Design of the Federal Institute of Piau?? (IFPI), in the Teresina Zona Sul and Piripiri campuses, with the main objective of understanding the teachers' and their perspectives on the cultural and epistemological dimensions of this area in relation to the technical and practical dimension, considering that their conceptions are reflected in their teaching practices, directly implying the formation of the students, future fashion designers for the world of work. We used as a methodological instrument the questionnaire, according to the Likert model, composed mostly of closed questions of objective response and, to a lesser extent, open questions of a subjective nature applied to the teachers of the course, as well as analysis of the documents that guide the technological education in Brazil, such as the CNE / CP no. 292/2002, which deals with the National Curriculum Guidelines at the Technologist Level and the National Catalog of Higher Education Courses developed by the Ministry of Education; we also analyze the pedagogical project of the Higher Course of Technology in Fashion Design of the IFPI in order to understand how the directions about fashion teaching in Brazil are characterized. This research discusses the importance of the cultural and epistemological dimensions of fashion in higher education teaching, proposes the scientific and academic legitimacy of this area and its recognition as a field of knowledge, or area of knowledge, in Brazil. These are urgent measures for your affirmation and growth. In the results, it was verified that the IFPI fashion professors have a vision on this area more focused on the technique, the practices and technologies and very little returns to the cultural and epistemological dimension of fashion. We found that this too technical and technological conception is not restricted to the IFPI teachers and the pedagogical project of the higher technology course in Fashion Design of this institution. This conception is also present in the structuring documents of the technological graduation, in documents of the MEC and CNE, demonstrating that there is a need not only local, but national, of change in the paradigms of technological teaching of fashion in Brazil.